Debate intercultural y antropología en latinoamerica: Presentación - Fuller, Norma (Pontificia Universidad Católica del Perú. Fondo Editorial, 2003)
Presentation of the dossier on intercultural debate and anthropology in Latin America.

Presentación al dossier sobre debate intercultural y antropología en latinoamerica.
Intercultural debate and anthropology in Latin America: A presentation
Keywords: Antropología; https://purl.org/pe-repo/ocde/ford#5.04.03